Поширення та життєздатність трьох представників роду Picea А. Dietr. у придорожніх насадженнях м. Кривий Ріг - Shevchuk, N.Yu.; Husejnova, E.R.; Korshykov, I.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to analyze the viability of three representatives of the genus Picea A. Dietr. in linear and roadside plantations of Kryvyi Rih to determine the prospects for their further use in landscaping of the cities of Steppe Dnieper Area. Material and methods. We investigated the state of the plantations formed by three representatives of the genus Picea in six administrative districts of Kryvyi Rih. Using the route method, we determined location of these plantations, number of individuals in them, age, trunk diameters as well as height of the trees. Approximate age of conifers was determined by the number of whorls and by external characters (color of needles, crown shape, tree height and trunk diameter). Results. It was established, that, in linear plantations along highways and in plantation groups on the roadside territories of Kryvyi Rih city, the most commonly found are such trees: P. pungens ‘Glauca’ – 4038 trees (58.8%), P. pungens – 1186 trees (17.3%) and P. abies – 1643 trees (23.9%). Most trees of all the three taxa belong to the age group of 30–40 years, and the vital state of different age plants in the vast majority of them can be categorized as «healthy». The significant role in the city greening is played by P. pungens ‘Glauca’ due to its high adaptive ability and decorativeness. Conclusion. Due to a set of biometric parameters, P. pungens, P. pungens ‘Glauca’ and P. abies are quite resistant to the urbotechnogenic environment of Kryvyi Rih and have good prospects for their further use in the city greening.